Development and performance analysis of novel design 3-DOF non-integrated runner permanent magnet spherical motor - Öğülmüş, Ahmet Saygın; Tınkır, Mustafa (Engineering science and technology, an international journal, 2023)
[Display omitted] The main objective of this research is to present a novel design of three degrees of freedom (DOF) non-integrated runner permanent magnet spherical motor (NR-PMSM). In this proposed spherical motor, tilting and spinning movements are separated from each other instead of integrated motion, thus providing a more ergonomic design, easier control and increasing working performance. The NR-PMSM body block consists of stator, rotor and two covers and differs from known spherical motors with its modular design and different rotor bearings. Iron core stators are mounted separately on ABS blocks to create a lighter mid-motor body. A multi-point ball bearing mechanism is provided between the lower and upper covers, and in this way, more stable movement of the rotor is ensured without affecting the electromagnetic structure of the motor. Matlab and Ansys/Maxwell finite element programs are utilized in the electromagnetic modeling and numerical calculations of the spherical motor. At the end of all these works, the NR-PMSM prototype is realized and the angle, torque, power and speed tests of the motor are carried out by experimentally and they are compared with the simulation results. As a result of the experimental study, NR-PMSM consumes 197 W of power at a maximum speed of 156 r/min. It produces 0.04 kgf.cm spinning torque per watt consumed, tilting torque of 0.031 kgf.cm. The motor weight is 0.730 kg and it produces 10.5 kgf.cm spinning, 8.7 kgf.cm tilting torque per kg. The rotor can rotate around 360 0 full lap while moving with a maximum tilting angle of ±45°. It is possible to summarize the subject of this study, novel design NR-PMSM is completely different and original from the spherical motor researches in the literature and it can be preferred in robotic/manipulator/simulator applications as a innovative actuator system.